UNIVERSITY EDUCATION SHOULD BE FREE - Munisa Nazirova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
ABSTRACT: This article explores the question of whether university education should be free. It examines the arguments in favor of and against free university education, considers alternative approaches to address education costs, and provides a comprehensive analysis of the topic. By weighing the potential benefits of increased access and equality against the potential drawbacks, this article aims to contribute to the ongoing discussion surrounding the affordability and accessibility of higher education.